A stable isotope study of the hydrological and carbon cycle in meromictic lake, Lovojärvi - Mutyaba, Colline (2012)
Lake Lovojärvi, at its deepest point of 17.5 m, is permanently stratified forming two water layers. The mixolimnion (the upper layer, from 0 to 10 m depth) is affected by seasonal changes while the monimolimnion (bottom layer, from 10 to 17.5 m depth) does not mix and is not affected by seasonal changes. As a result, the lake stores large quantities of dissolved inorganic carbon and methane. I used a multiple stable isotope approach to gain insight into the carbon cycle and water balance of Lovojärvi. The δ18O and δ2H profiles reveal that at the 7 m depth in the mixolimnion, there is a sub-surface stream whose isotopic characteristics are similar to surface streams from a nearby mire, suggesting that this water could be coming from the mire. Measurements of δ13C-DIC and of concentrations of DIC and CH4 were used to trace carbon flow in the lake. Variations in the epilimnion of DIC concentration and of δ13C-DIC (ranging from -15.42 to -5.75‰) are explained by photosynthesis, while the strongly enriched 13C-DIC and high concentrations of DIC and CH4 in the deep water are explained by organic matter oxidation and methanogenesis. Methanotrophy appears to be an important source of carbon to the food web evidenced by the depleted 13C-zooplankton (-38.2‰).